Sosialisasi Entrepreneurial Learning di Sekolah untuk Meningkatkan Kompetensi dan Jiwa Kewirausahaan Siswa di SMK N 8 Padang - Yozi Putri Sakinah; Meissy Putri Deswari; Yelva Nofriyanti; Muhammad Farrasky Delas Putra; Evi Desmarian (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
The unemployment rate among SMKs is not balanced with the increasing number of SMK One of the causes of increased unemployment is due to the implementation of an education system that still emphasizes theory compared to practice. Therefore, it is important to improve the identity of prospective SMK graduates who have high quality human resources, skills and are able to compete, for example through entrepreneurship and digital marketing education. Students' interest in entrepreneurship is influenced by the lack of entrepreneurial spirit within them. Entrepreneurial skills are an ability that a person has as a form of assigning knowledge and applying it to real activities in his life. Efforts to realize these goals at the SMK level have been developed and implemented in entrepreneurship subjects in the national curriculum for vocational secondary levels. Then today's SMK students who grew up with technology, internet and social media have a preference to start an entrepreneurship. Some of the reasons high school students choose the entrepreneurial path are unwilling to be limited, college is not a guarantee of success, freelance and peer-to-peer service sites, ubiquitous social media, abundant access, and mentors.